PENGARUH PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR PESERTA DIDIK - admin, admin; Nuraeni, Rikeu Siti; Hasanudin, Nurullah (Prodi PAI IAILM Suryalaya, 2021)
This study aims to determine the effect of parents attention on student achievement in MIN 12 Ciamis. The method used in this study is a descriptive method with a quantitative approach, with a population of 401 people, and a sample of 51 people which is taken by using purposive sampling technique, and using data collection techniques namely questionnaires, observation, and documentation. Based on the result of data processing it is obtained that the attention of parents of students in MIN 12 Ciamis is quite good (Mean = 83,3 on a scale of 90,2 – 82,4 with good classification). While the learning achievement of student in MIN 12 Ciamis is quite sufficient (Mean = 78 is on the interpretation scale 84 – 75 with sufficient classification). And the influence of parents attention on student achievement in MIN 12 Ciamis has a significant positive effect on the moderate category, it is proven that rs = 0,56 is at an interval of 0,41 – 0,60 and tcount (4,72) is greater than t table (1,68). The attention of parents determines students achievement by 31% while the remaining 69% is determined by other factors.